Hubungan Pola Hidup Masyarakat Pesisir dengan Angka Kejadian Penyakit Diabetes Melitus dan Asam Urat - Cahyo Wulandari; Muhammad Asyam Fawwaz Akbar; Rahmafari Fikra Maulida (Direktorat Pengabdian kepada Masyarakat, 2023)
Non-communicable diseases (NCDs) have become a global health problem, including in Indonesia itself, where the death rate caused by NCDs is quite high. One of the NCDs that is often found in society is diabetes mellitus and gout. An integrated coaching post (posbindu) was implemented as a NCDs prevention program targeting people aged 15–60 years. Posbindu has been running regularly in three villages where the UGM KKN-PPM unit JT-133 is located, namely Tedunan Village, Wedung Village, and Tempel Village. This research method is to collect data from health test results, is processed descriptively and quantitatively, and short anamnesis results (qualitative data) to explore the risk factor. The characteristics of the Posbindu participants examined were 14% men and 86% women, with ages ranging from 20 to 60 years, with details of the age group 19–44 being 53% and 45–60 years being 47%. Apart from that, the body mass index (BMI) of Posbindu participants was 47% normal, while 49% were obese. When examining the blood sugar of the obese group aged 19-44 years, there was an increase in blood sugar levels and the incidence of diabetes, compared to the non-obese group in the same age group. In the uric acid examination, it was found that the incidence of hyperuricemia in the 19-44 years age group was related to the incidence of obesity and certain eating patterns. From these data it can be concluded that one of the causes of diabetes mellitus and gout in the 19-44 years age group is lifestyle. The unhealthy lifestyle of coastal communities in these three villages includes lack of physical activity, excessive consumption of foods and drinks high in sugar, and others. Therefore, promoting a healthy lifestyle wherever and whenever, especially during posbindu, is the main key in preventing and treating NCDs.